From the Editors - Esterhuyse, Abel; Liebenberg, Ian (Scientia Militaria - South African Journal of Military Studies, 2014)
The use of armed force, Clausewitz argues, has its own grammar but not its logic. In general, most military practitioners have a sound understanding of the nature of the political process that underpins the logic of war. At the same time, though, they tend to view politics with scepticism because politicians “… by virtue of their craft, perceive or fear wide ramifications of action, prefer to fudge rather than focus, and like to keep their options open as long as possible by making the least decision as late as feasible”.1 Instead of muddling through, the military realm, in contrast, is perceived as an orderly world set to “… simplify, focus, decide, and execute”.2 The reality of the military grammar that Clausewitz refers to, of course, is somewhat different. More specifically, it would be more correct to speak of the grammars of war since warfare, as the manifestation of war, displays itself in a number of ways. This is precisely the reason why Clausewitz advises, The first, the supreme, the most far-reaching act of judgment that the statesman and commander have to make is to establish … the kind of war on which they are embarking; neither mistaking it for, nor trying to turn it into, something that is alien to its nature. This is the first of all strategic questions and the most comprehensive.3